Deep-sea prosobranch molluscs in Northwest Africa - Castillo, Sara; Ramil, Francisco; Mohamed Moctar, S.M.; Ramos, Ana (2015)
The aim of this work is the study of the prosobranch molluscs collected during the 11 research surveys carried out in Northwest Africa onboard R/V Dr. Fridtjof Nansen and R/V Vizconde de Eza between 2002 and 2012, within the framework of the EcoAfrik and the FAO EAF-Nansen projects. The working area extended from Cape Spartel (Gibraltar Strait) to Guinean coasts, and includes 1350 trawling stations deployed between 100 and 1748 m depth. The samples were collected using mainly a commercial otter trawl and a beam-trawl in soft bottoms; a rock dredge was also employed for the study of hard bottoms located along the Mauritanian slope. Prosobranchs were collected in 483 stations, representing 36% of the sampled stations. Preliminary identifications reported about 120 species belonging to 29 different families; Muricidae, Naticidae and Nassariidae showed the highest specific richness within the families. The most frequent species were Xenophora crispa in Morocco, Charonia lampas in Western Sahara, Nassarius wolffi in the area stretching between Cape Blanc (Mauritania) and Cape Verde (Senegal), and Stellaria testigera digitata in the southern zone. The analysis of bathymetric distributions reveals a progressive decreasing of specific richness with increasing depth. Abundance and biomass remained constant up to 500 m but sharply dropping beyond this depth. Deeper than 1400 m prosobranch were not collected.